Microbiological and Chemical Quality of Keropok Lekor during Processing And Storage - Mahmud @ Ab. Rashid, Nor Khaizura (2008)
Keropok lekor is an important fish product in Malaysia. The customers’ demands for keropok lekor have been increasing. This study was conducted to analyze the microbiological and chemical quality of keropok lekor in every stage of its processing, namely mincing, mixing, kneading, boiling and cooling. Subsequently, this study was also undertaken in an attempt to determine the effectiveness of post processing treatment on keropok lekor in order to prolong its shelf life. The method used to analyze the microbiological quality is known as the direct plate counts for the total plate counts (TPC), psychrotrophic, yeasts and molds, mesophilic sporeformer, Staphylococcus aureus, total coliform and fecal coliform counts. Simple biochemical test was carried out to identify the presumptive bacteria present in keropok lekor processing. Chemical quality was analyzed on the total volatile bases (TVB) and trimethylamine (TMA), using Conway microdiffusion method, and biogenic amines was done using the High Performance Liquid Chromatography (HPLC). The post-processing treatments on keropok lekor were exposing keropok lekor to UV light for 15 or 30 min, either coated with different concentrations of ascorbic acid (500, 1000 or 1500 ppm) or dipped in hot oil for 3, 6 or 9 s, and stored at the room temperature for 7 d or at chill temperature (4±1°C) for 14 d. When processing keropok lekor, the boiling of keropok lekor at 100°C for 10 min reduced the TPC (4.38±0.47 log10 cfu/g), psychrotrophic counts (2.00 ± 0.00 log10 cfu/g), mesophilic sporeformer counts (1.26 ± 0.34 log10 cfu/g) and total coliform counts (1.71±0.51 log MPN/g) significantly (p>0.05). However, the microbial counts were found to increase significantly (p<0.05) after the cooling process, except for the yeast and mold counts and S. aureus counts. The presumptive predominant microorganisms, isolated before the boiling stage, were members of the Enterobacteriaceae family and those belonging to Pseudomonas, Vibrio, Staphylococcus, Bacillus and Micrococcus genus. After the boiling stage, the presumptive predominant microorganisms were members of Enterobacteriace family and those belonging to Micrococcus, Bacillus, Staphylococcus and Aerococcus genus. As for the chemical quality, TVB and TMA levels were indicated to significantly decrease (p<0/05) after boiling from 7.29 to 4.68 mg/ 100g and 3.38 to 1.81 mg/ 100g, respectively, but not for the putrescine, cadaverine and histamine levels. Before the boiling stage, presumptive microorganisms producing putrescine, cadaverine and histamine were members of the Enterobacteriaceae family, as well as members of Staphylococcus, Pseudomonas and Micrococcus genus. Members of the genus Pseudomonas, which produce biogenic amines, were not isolated from keropok lekor after the boiling stage. The post-processing treatment which was applied on keropok lekor was found to enhance both its quality and shelf life. The results showed that exposing keropok lekor to UV light for 15 min and dipping it in hot oil for 9 s had extended the shelf life of this snack for 5 d when v stored at the room temperature, and for 14 d when stored at 4±1°C. This post processing treatment had also caused a significant reduction in TPC, psychrotrophic count, yeasts and molds count, TVB, as well as TMA and putrescine, cadaverine and histamine level. On the contrary, ascorbic acid was not as effective in increasing the shelf life of keropok lekor or in reducing TVB, TMA and putrescine, cadaverine and histamine level, as compared to dipping it in hot oil.